O totalitaryzmie z perspektywy encykliki „Centesimus annus” Jana Pawła II - Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The study presents the assumptions of totalitarian ideology and the effects of its occurrence in the third social encyclical of John Paul II — ”Centesimus annus,” which was published in 1991. The focus was on defining the papal vision of abuses and violations that were the result of the functioning of totalitarian structures in selected countries. Attention is paid to various forms of limitations experienced by an individual deprived of the ability to fulfil his or her own needs and aspirations. It was emphasized that among the most serious, degrading effects of the functioning of a totalitarian state for man, we should point out deep anti-personalism and anthropological reductionism. The Pope’s arguments were presented concerning the conditions that can make democracy only a seemingly “safe” political system.
Keywords: totalitaryzm; encyklika; Centesimus annus; społeczna nauka Kościoła; godność jednostki